2012
DOI: 10.1167/iovs.11-8869
|View full text |Cite
|
Sign up to set email alerts
|

Important Role of Epiregulin in Inflammatory Responses during Corneal Epithelial Wound Healing

Abstract: PURPOSE. To investigate the role played by epiregulin in corneal epithelial wound healing in vivo in epiregulin-knockout (KO) mice and cultured mouse corneal epithelial cells (MCECs). METHODS.A 2-mm diameter central epithelial wound was created in epiregulin-KO and wild-type (WT) mouse corneas. The size of the unhealed area and the epithelial cell proliferation and migration were examined. Myeloperoxidase assay was performed to determine the number of polymorphonuclear (PMN) cells infiltrating corneal stroma. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…To investigate the mechanism of TM expression in the process of corneal epithelial wound healing, primary MCECs were isolated and cultured via previously reported methods [ 19 , 21 , 22 ], with some modifications. We confirmed that the MCECs (third passage) expressed TM and the corneal epithelium specific marker K12 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the mechanism of TM expression in the process of corneal epithelial wound healing, primary MCECs were isolated and cultured via previously reported methods [ 19 , 21 , 22 ], with some modifications. We confirmed that the MCECs (third passage) expressed TM and the corneal epithelium specific marker K12 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Epiregulin (EREG) is a recently identified member of the epidermal growth factor family of ligands with functions in inflammation and wound healing (42). In mice, EREG is also known to play a critical role in corneal wound healing (43). A potential therapeutic strategy of co-administering glucocorticoids and epiregulin might offer a beneficial outcome in cases of corneal injury.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a single injury to the cornea causes greater corneal opacity and greater corneal infiltration by polymorphonuclear cells in epiregulin-null mice than in normal mice. Likewise, epiregulin-null mice also exhibit defects in the responses to repetitive corneal injuries [58]. …”
Section: The Roles Of Epiregulin In Inflammation Wound-healing Anmentioning
confidence: 99%